2017
DOI: 10.1038/s41598-017-03097-x
|View full text |Cite
|
Sign up to set email alerts
|

Fused Deposition Modeling (FDM) 3D Printed Tablets for Intragastric Floating Delivery of Domperidone

Abstract: The aim of this study was to explore the feasibility of fused deposition modeling (FDM) 3D printing to prepare intragastric floating sustained release (FSR) tablets. Domperidone (DOM), an insoluble weak base, was chosen as a model drug to investigate the potential of FSR in increasing its oral bioavailability and reducing its administration frequency. DOM was successfully loaded into hydroxypropyl cellulose (HPC) filaments using hot melt extrusion (HME). The filaments were then printed into hollow structured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(141 citation statements)
references
References 30 publications
(38 reference statements)
2
131
1
7
Order By: Relevance
“…This type of composition can be used to produce a wide range of modified release drug delivery systems cost-effectively. Previous studies have successfully used HPC to produce Polymers 2020, 12, 27 4 of 18 drug-loaded filaments for the 3D printing of tablets [11,41,42]. However, HPC itself is hygroscopic, causing HPC-based filaments to have very short usage life [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of composition can be used to produce a wide range of modified release drug delivery systems cost-effectively. Previous studies have successfully used HPC to produce Polymers 2020, 12, 27 4 of 18 drug-loaded filaments for the 3D printing of tablets [11,41,42]. However, HPC itself is hygroscopic, causing HPC-based filaments to have very short usage life [43].…”
Section: Introductionmentioning
confidence: 99%
“…This means the maximum efficiency of the drug can be obtained as the storage time is minimised and hence degradation can also be minimised [9]. Since the U.S. Food and Drug Administration's (FDA) approval of the first 3D printed drug, Spritram ® , there has been plenty of research that involves the 3D printing of various types of drug delivery systems [10][11][12]. The most easily accessible and low-cost 3D printing is fused deposition modelling (FDM).…”
mentioning
confidence: 99%
“…Similarly, the specific strength of the GPLA is found to be 5.422 MPa and PETG to be 3.42MPa as shown in figure 11. From the observation it is found that the specific strength of GPLA with 15% infill is higher to that of PTEG resulting in enhanced properties of GPLA and PETG [16].…”
Section: Specific Strength Of Gpla and Petgmentioning
confidence: 96%
“…For instance, channelled tablets show an accelerated drug release due to the increased surface area to volume ratio [10], while a multi-block tablet design results in a quicker fragmentation compared to no-gaps devices, thus avoiding the need for a disintegrant [11]. A further example is altering tablet density by varying the infill percentage in fused deposition modelling (FDM) 3D printed tablets; as a result, different drug release profiles can be achieved without modifying the formulation [12,13]. The advantages of such approach are significative, since dosage forms tailored on the needs of single patients could be manufactured at a moment using the same equipment and feedstock material, with a positive outcome on treatments costs.…”
Section: Tuning Dosage Form Properties Through Digital Designmentioning
confidence: 99%